Analisis Kualitas Jaringan Internet Wireless LAN PT. Teladan Prima Agro - Ahmad Ridhani Mubaraq; Naufal Azmi Verdikha; Muhammad Taufiq Sumadi (Jurnal Publikasi Teknik Informatika, 2024)
The internet or interconnected networking is a network that connects computers of various types that form a network system that covers the entire world. This research aims to determine the quality of the internet network of PT Teladan Prima Agro (PT TPA). The research method used is Quality Of Service (QoS) with data retrieval techniques using Wireshark software. The results showed that the average QoS index of the PT. TPA office internet network based on the TIPHON standard obtained the result "Satisfactory". From the research results it can be concluded that the average level of internet network quality in the PT. TPA office area is in the good category and can support the performance of staff / employees in transferring data.